On affine tropical F5 algorithms. (January 2021) - Vaccon, Tristan; Verron, Thibaut; Yokoyama, Kazuhiro
Abstract: Let K be a field equipped with a valuation. Tropical varieties over K can be defined with a theory of Gröbner bases taking into account the valuation of K . Because of the use of the valuation, the theory of tropical Gröbner bases has proved to provide settings for computations over polynomial rings over a p -adic field that are more stable than that of classical Gröbner bases. Beforehand, these strategies were only available for homogeneous polynomials. In this article, we extend the F5 strategy to a new definition of tropical Gröbner bases in an affine setting. We also provide a competitor with an adaptation of the F4 strategy to tropical Gröbner bases computations. We provide numerical examples to illustrate time-complexity and p -adic stability of this tropical F5 algorithm. We also illustrate its merits as a first step before an FGLM algorithm to compute (classical) lex bases over p -adics.